Interpretation of Spatial-Temporal Patterns of Community Green Spaces Based on Service Efficiency and Distribution Characteristics: A Case Study of the Main Urban Area of Beijing, China - Xiaoyi Zu; Zhixian Li; Chen Gao; Yi Wang (ISPRS International Journal of Geo-Information, 2022)
Urban-scale green spaces have been a central topic as of late, but community-scale green spaces are overlooked in urban studies. This paper takes community green spaces in the main urban area of Beijing as the case to quantitatively interpret the spatial-temporal patterns of their service efficiency and distribution characteristics. The measurement section of the paper includes two parts: the first part compares the applicability of two major green space service efficiency measurement methods on the community scale and determines that the Shortest Time Distance method performs better in describing the spatial-temporal patterns of service efficiency. The second part applies the Time Distance Entropy method to initially identify the locational relationship between community green spaces and neighboring residential buildings, then proposes the Green Space Distribution Coefficient method based on this relationship to analyze the ‘courtyard’, ‘mixed’, and ‘centralized’ distribution types alongside the transition relationships between them, and the spatial-temporal patterns of distribution characteristics are measured. The results of service efficiency reveal that the community paradigms transform from ‘humanistic-oriented’ to ‘benefit-oriented’ as the Shortest Time Distance measurement values show an ascending trend with the passage of years and the outward expansion of the ring roads. The results of distribution characteristics reveal that the community residential culture transforms from ‘closeness’ to ‘detachment’ as Green Space Distribution Coefficient measurement values show a descending trend under the same conditions. Based on the measurements, this paper further provides several optimizing strategies for community green spaces in the central urban area of Beijing.